Whole-genome analysis of an extensively drug-resistant clinical isolate of Acinetobacter baumannii AC12: Insights into the mechanisms of resistance of an ST195 clone from Malaysia - Zarizal, Suhaili; Soo Sum, Lean; Chew Chieng, Yeo (Elsevier, 2015)
Acinetobacter baumannii has emerged as an important nosocomial pathogen owing to its increasing resistance to most, if not all, antibiotics in clinical use. We recently reported the occurrence of extensively drug-resistant (XDR) A. baumannii isolates in a Malaysian tertiary hospital. The genome of one of these XDR isolates (A. baumannii AC12) was completely sequenced and comparative genome analyses were performed to elucidate the genetic basis of its antimicrobial resistance. The A. baumannii AC12 genome consists of a 3.8 Mbp circular chromosome and an 8731 bp cryptic plasmid, pAC12. It belongs to the ST195 lineage and is most closely related to A. baumannii BJAB0715 as well as other strains of the international clone III (IC-III) group. Two antibiotic resistance islands (RIs), designated AC12-RI1 and AC12-RI2, were found in the AC12 chromosome along with a 7 kb Tn1548::armA island conferring resistance to aminoglycosides and macrolides. The 22.8 kb AC12-RI1 interrupts the comM gene and harbours the carbapenem resistance gene blaOXA-23 flanked by ISAba1 within a Tn2006-like structure. AC12-RI1 also harbours resistance determinants for aminoglycosides, tetracyclines and sulphonamides. The 10.3 kb IS26-flanked AC12-RI2 is a derivative of AbGRI2-1, containing aphA1b and blaTEM genes (conferring aminoglycoside and β-lactam resistance, respectively). The presence of numerous genes mediating resistance to various antibiotics in novel RI structures as well as other genes encoding drug transporters and efflux pumps in A. baumannii AC12 most likely contributed to its XDR characteristics.